Electrode material, positive electrode film and preparation method and application thereof

By employing a carbon nanotube cross-linked three-dimensional network structure and a polycrystalline microsphere composite electrode material with fluoride ions replacing zinc manganate unit cells in an aqueous zinc-ion battery, the conductivity and ion diffusion problems of the cathode material were solved, resulting in a high-performance improvement in battery performance.

CN120914236APending Publication Date: 2025-11-07JILIN INST OF CHEM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511114813.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing aqueous zinc-ion battery cathode materials suffer from irreversible structural transformation, Mn3+ disproportionation reaction, poor conductivity, and slow ion diffusion, leading to a decrease in charge and discharge capacity.

Method used

A three-dimensional network structure composed of cross-linked carbon nanotubes is used as the matrix, and polycrystalline microspheres of zinc manganate with oxygen elements replaced by fluoride ions are distributed on the matrix. Through chemical bonding, a composite electrode material is formed, which improves ion transport rate and conductivity.

Benefits of technology

It significantly improves the conductivity and ion transport rate of electrode materials in aqueous zinc-ion batteries, enhances structural stability, and improves the overall performance of the battery, especially the battery capacity retention rate under high cycle counts and high current densities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914236A_ABST
    Figure CN120914236A_ABST
Patent Text Reader

Abstract

The electrode material comprises a three-dimensional network matrix formed by crosslinking of a plurality of carbon nanotubes and a plurality of polycrystalline microspheres distributed on the three-dimensional network matrix, the polycrystalline microspheres are obtained by crystallization of a plurality of zinc manganate unit cells, and at least one oxygen element of the zinc manganate unit cells is substituted by fluorine ions. Comprising the electrode material, carbon nanotubes and a nanocellulose membrane, and the electrode material and the carbon nanotubes are loaded in the nanocellulose membrane and are uniformly distributed. According to the electrode material, the three-dimensional network structure formed by crosslinking of the carbon nanotubes is used as a matrix, the polycrystalline microspheres obtained by crystallization of the zinc manganate unit cells with at least one oxygen element substituted by the fluorine ions are distributed on the matrix, and the fluorine ions are introduced to replace part of the oxygen element, so that the ion transport rate is remarkably improved, and the internal resistance is reduced; by bonding the carbon nanotubes, the transmission kinetics of Zn < 2 + > is promoted, the conductivity and the ion transmission rate of the material are remarkably improved, and the material can be used for improving the performance of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of materials, in particular to an electrode material, a positive electrode film and a preparation method and use thereof. BACKGROUND

[0002] The rapid development of science and technology has greatly changed the way of human life, and at the same time, the demand for energy in society has increased. With the increasing demand for sustainable energy, energy storage technology has become a hot topic of current research. Lithium ion batteries have achieved great success in the current energy storage market, but due to the limited reserves of lithium and the use of flammable and explosive organic electrolytes, lithium ion batteries have a higher risk, which limits their further development. Among the many energy storage systems to solve energy problems, aqueous zinc ion batteries (AZIB) have become one of the promising candidates to replace lithium ion batteries due to their low cost, high safety and affordability.

[0003] Zinc anode has a high theoretical discharge capacity (820 mAh·g -1 ) and a low operating potential (-0.76 V vs. standard hydrogen electrode (SHE)). However, compared with the large theoretical specific capacity of zinc anode, the reported cathode materials are unsatisfactory, with low capacity and further improved cycle stability. Many cathode candidates have been studied for AZIB, including vanadium-based materials, prussian blue analogues and manganese-based materials, among which manganese-based oxide materials generally have a higher operating voltage and excellent theoretical specific capacity, which helps to improve the energy density. ZnMn2O4, which has a spinel structure similar to LiMn2O4, is a popular manganese-based oxide cathode material in the study of AZIB cathode materials due to its abundance and low toxicity. However, ZnMn2O4 has some problems, such as irreversible structural transformation and disproportionation of Mn 3+ , which leads to a rapid decrease in capacity during charging and discharging, and also has the problems of poor intrinsic conductivity and slow ion diffusion.

[0004] Therefore, how to design a low-cost and high-performance electrode material for aqueous zinc ion batteries is a technical problem that needs to be solved by those skilled in the art. SUMMARY

[0005] One of the purposes of the present application is to overcome the shortcomings of the prior art, and to provide an electrode material, in which a three-dimensional network structure formed by cross-linking carbon nanotubes is used as a matrix, and a plurality of polycrystalline microspheres obtained by distributing a zinc manganate crystal cell in which at least one oxygen element is replaced by a fluorine ion on the matrix are provided. By replacing part of the oxygen elements with fluorine ions, the ion transport rate is significantly improved, and the internal resistance is reduced. By bonding carbon nanotubes, Zn2 +The transmission kinetics of the electrode material is improved, the conductivity and ion transmission rate of the material are improved, and the overall performance of the aqueous zinc ion battery can be improved.

[0006] The second purpose of the present application is to provide a positive electrode film prepared by using the above electrode material, which can provide a strong and flexible support, enhance the structural stability, and establish an effective channel for the transportation of electrons and ions, thereby promoting the transportation of ions / electrons.

[0007] The technical solution for achieving one of the purposes of the present application is an electrode material, comprising a three-dimensional network matrix composed of a plurality of cross-linked carbon nanotubes, and a plurality of polycrystalline microspheres distributed on the three-dimensional network matrix, wherein the polycrystalline microspheres are obtained by crystallizing a plurality of zinc manganate unit cells in which at least one oxygen element is replaced by fluorine ions.

[0008] Further, the plurality of polycrystalline microspheres are combined with the carbon nanotubes of the three-dimensional network matrix by chemical bonds, and the oxygen elements in 1 mol of zinc manganate unit cells are replaced by 3 mol of fluorine ions.

[0009] The preparation method of any of the above electrode materials comprises the following steps:

[0010] 1) Take manganese acetate and zinc acetate, and dissolve them in ethanol;

[0011] 2) Add carbon nanotubes and disperse them evenly;

[0012] 3) Add fluorine salt and stir evenly;

[0013] 4) After hydrothermal reaction, the target electrode material F-ZnMn2O4 / CNT is obtained.

[0014] Preferably, in step 1), the molar ratio of zinc acetate to manganese acetate is 1:2, in step 2), the concentration of carbon nanotubes is 0.4 mg / ml, in step 3), the added fluorine salt is ammonium fluoride, the molar ratio of ammonium fluoride to zinc acetate is 1-4:1, the stirring time is 30 min-60 min, in step 4), the hydrothermal reaction temperature is 180℃, the reaction time is 12h, after hydrothermal reaction, the solution is cooled to room temperature, centrifuged and washed, dried to obtain the target electrode material, the centrifugation is performed at 13000 rpm for 15 min, the washing is performed by using deionized water and ethanol alternately, the centrifugation is performed for 3 times, and the solution is treated by vortex and ultrasonic before centrifugation, and the drying is performed at 60-80℃ for 4h-6h.

[0015] The technical solution for achieving the second purpose of the present application is a positive electrode film, comprising any of the above electrode materials, carbon nanotubes, and a nanocellulose film, wherein the electrode material and the carbon nanotubes are loaded in the nanocellulose film and are uniformly distributed.

[0016] Preferably, the mass ratio of the carbon nanotubes to the nanocellulose is 2:1; the loading amount of the electrode material on the nanocellulose film is 1 mg / cm2, and the thickness of the nanocellulose film is 10-150 μm.

[0017] The preparation method of any of the above positive electrode films comprises the following steps:

[0018] 1) ultrasonically dispersing any of the above-prepared electrode materials and carbon nanotubes in a nanocellulose aqueous dispersion;

[0019] 2) suction filtration to form a film, and drying to obtain a positive electrode film.

[0020] Preferably, the concentration of the nanocellulose aqueous dispersion in step 1) is 0.1 wt%, and the concentration of the carbon nanotubes is 0.2 wt%; and the drying in step 2) is hot-press vacuum drying, the drying temperature is 60-80℃, and the drying time is 10-12 h.

[0021] The application also provides the use of the above positive electrode film in the preparation of a battery.

[0022] Further, the battery is a water-based zinc ion battery, the positive electrode of the water-based zinc ion battery is the positive electrode film of claim 5 or 6, the negative electrode is a zinc sheet, the separator is a glass limiting separator, and the electrolyte is an aqueous solution of a zinc sulfate and manganese sulfate mixture with concentrations of 2M and 0.2M, respectively.

[0023] The above technical solution has the following beneficial effects:

[0024] 1. The electrode material provided by the application comprises a three-dimensional network matrix composed of a plurality of crosslinked carbon nanotubes, and a plurality of polycrystalline microspheres distributed on the three-dimensional network matrix, the polycrystalline microspheres are obtained by crystallizing a plurality of at least one oxygen element substituted with fluorine ions zinc manganate unit cells, the carbon nanotubes are chemically bonded to the surface of the doped crystal to form a composite, the carbon nanotubes provide an excellent conductive network structure, and as a carrier for loading polycrystalline microspheres, the structure of the F-ZnMn2O4 crystal after doping has not changed, the doped fluorine ions can significantly improve the ion transport rate of the doped crystal and reduce the internal resistance, the fluorine ion doping also expands the interplanar spacing, making the crystal structure loose, which allows more Zn2+ to be stored, greatly improving the electrode capacity of the crystal, and thus the overall performance of the water-based zinc ion battery can be improved.

[0025] 2. The preparation method of the electrode material has the advantages of mild reaction conditions and simple process, and is conducive to industrial large-scale production.

[0026] 3. The positive electrode film provided by the application forms a reticular matrix with nanocellulose, and the electrode material and carbon nanotubes are uniformly loaded in the reticular matrix to form the positive electrode film. The nanocellulose has the advantages of high specific surface area, excellent mechanical strength, good chemical compatibility, and excellent electrical conductivity of carbon nanotubes, which are synergistically integrated. The composite structure not only provides a strong and flexible support for the positive electrode material and enhances the structural stability, but also establishes an effective channel for the transportation of electrons and ions, and promotes the transportation of ions / electrons.

[0027] 4. The preparation method of the positive electrode film has the advantages of mild reaction conditions and simple process, and is beneficial to industrial large-scale production.

[0028] According to the applicant's test verification, the aqueous zinc ion battery prepared by using the positive electrode film has a battery capacity retention rate of 96% or more and a discharge specific capacity of 335.2 mAh / g or more after 1000 cycles at a current density of 3 A / g.

[0029] The application will be further described below in combination with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF DRAWINGS

[0030] Figure 1 EDS-mapping image of the electrode material of Example 1 F-ZnMn2O4 / CNT;

[0031] Figure 2 SEM image of the electrode material of Example 1 F-ZnMn2O4 / CNT;

[0032] Figure 3 XRD image of the doped zinc manganate material and the zinc manganate material;

[0033] Figure 4 TDOS and PDOS images of the doped zinc manganate material and the zinc manganate material;

[0034] Figure 5 Battery rate performance image of Example 4-6 and Comparative Example 2;

[0035] Figure 6 Long cycle image of the battery of Example 4 at a current density of 3 A / g. DETAILED DESCRIPTION

[0036] In the present application, the zinc sulfate (Zn(Ac)2), manganese sulfate (Mn(Ac)2), zinc acetate (ZnSO4), manganese acetate (MnSO4), urea and multi-walled carbon nanotubes used are purchased from China Aladdin Company, ammonium fluoride (NH4F) is purchased from China Macklin Company, and all the medicines are of analytical purity and without further purification. Zinc foil (99.99%) and watman glass fiber (GF-D) are purchased from the future (Jilin) material technology Co., Ltd., and corn straw is from farmers in northeast China. A Shanghai analysis vacuum circulating water pump is used for filtration operation; a BPZ-6092 vacuum oven produced by Shanying Scientific Instrument (Shanghai) Co., Ltd. is used for vacuum drying treatment. SHB-IIIA A Shanghai analysis vacuum circulating water pump is used for filtration operation; a BPZ-6092 vacuum oven produced by Shanying Scientific Instrument (Shanghai) Co., Ltd. is used for vacuum drying treatment.

[0037] Example 1 Preparation of F-ZnMn2O4 / CNT electrode material

[0038] 0.22g of zinc acetate (0.001mol) and 0.49g of manganese acetate (0.002mol) were weighed and dissolved in 50mL of anhydrous ethanol, after fully dissolving, 20mg of carbon nanotubes was added to the solution, ultrasonic for 30min to make it disperse uniformly, 0.111g of ammonium fluoride (0.003mol) was added, continue to stir for 1h, make it fully mixed, the fully mixed solution was transferred to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, hydrothermal reaction was carried out at 180℃ for 12h. When the reactor was completely cooled to room temperature, the product was taken out, washed and centrifuged with deionized water and anhydrous ethanol alternately for 3 times, dried at 80℃, and F-ZnMn2O4 / CNT electrode material was obtained.

[0039] Example 2 Preparation of F-ZnMn2O4 / CNT electrode material

[0040] 0.22g of zinc acetate and 0.49g of manganese acetate were weighed and dissolved in 50mL of anhydrous ethanol, after fully dissolving, 20mg of carbon nanotubes was added to the solution, ultrasonic for 30min to make it disperse uniformly, 0.037g of ammonium fluoride was added, continue to stir for 1h, make it fully mixed, the fully mixed solution was transferred to a stainless steel hydrothermal reactor with polytetrafluoroethylene lining, hydrothermal reaction was carried out at 180℃ for 12h. When the reactor was completely cooled to room temperature, the product was taken out, washed and centrifuged with deionized water and anhydrous ethanol alternately for 3 times, dried at 80℃, and F-ZnMn2O4 / CNT electrode material was obtained.

[0041] Example 3 Preparation of F-ZnMn2O4 / CNT electrode material

[0042] 0.22 g of zinc acetate and 0.49 g of manganese acetate were dissolved in 50 mL of anhydrous ethanol. After complete dissolution, 20 mg of carbon nanotubes were added to the solution, and the mixture was sonicated for 30 min to disperse it evenly. 0.074 g of ammonium fluoride was added, and the mixture was stirred for 1 h to ensure thorough mixing. The well-mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE) and subjected to a hydrothermal reaction at 180 °C for 12 h. After the reactor had completely cooled to room temperature, the product was removed, washed three times alternately with deionized water and anhydrous ethanol, and dried at 80 °C to obtain the F-ZnMn2O4 / CNT electrode material.

[0043] Comparative Example 1: Preparation of ZnMn2O4 / CNT electrode material

[0044] 0.22 g of zinc acetate and 0.49 g of manganese acetate were dissolved in 50 mL of anhydrous ethanol. After complete dissolution, 20 mg of carbon nanotubes were added to the solution, and the mixture was sonicated for 30 min to ensure uniform dispersion. The well-mixed solution was then transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE) and subjected to a hydrothermal reaction at 180 °C for 12 h. After the reactor had completely cooled to room temperature, the product was removed, washed three times alternately with deionized water and anhydrous ethanol, and dried at 80 °C to obtain the ZnMn2O4 / CNT electrode material.

[0045] The electrode material obtained in Example 1 was subjected to EDS and SEM scanning. The EDS and SEM images are shown in [reference 1]. Figure 1 , Figure 2 The electrode materials obtained in Example 1 and Comparative Example 1 were subjected to XRD tests and electronic structure analysis, such as... Figure 3 , Figure 4 As shown in the EDS image, F is uniformly distributed in the crystal. Figure 2 It can be seen that F-ZnMn2O4 / CNT is a successful composite of uniformly sized nanoparticles and carbon nanotubes, forming a well-conductive network. (Fluorine doping did not change its microstructure; however, its incorporation into the lattice significantly improved the material's conductivity and ion diffusion rate, thus optimizing the performance of the assembled battery.) Figure 3 Figure 4 The results show that both exhibit typical diffraction peaks of ZnMn2O4, corresponding to standard ZnMn2O4, and no impurity phase peaks are observed. This indicates that fluorine doping did not change the crystal structure, and that successful F doping caused a slight shift in the XRD peaks, proving that the structure is intact and the synthesis was successful.

[0046] Example 4: Preparation of an aqueous zinc-ion battery

[0047] Step one, preparation of the positive electrode: carbon nanotubes and F-ZnMn204 / CNT electrode material prepared in Example 1 were uniformly dispersed in 0.1wt% nanocellulose water dispersion after ultrasonic treatment, wherein the mass ratio of carbon nanotubes to nanocellulose was 2:1, and the dosage of the prepared F-ZnMn204 / CNT electrode material was 12.56 mg according to the size of the final electrode film. The solution was filtered into a film under the condition of negative pressure of 0.1 Mpa, and the positive electrode film was obtained after vacuum hot pressing drying at 80°C. The loading amount of F-ZnMn204 / CNT was 1 mg / cm 2 The final cutting was a positive electrode round piece with a diameter of 14 mm.

[0048] Step two, the zinc foil with a thickness of 150 μm and a purity of 99%~99.9% was polished with sandpaper to remove the surface oxide layer, and the polished zinc foil was cut into a round piece with a diameter of 12 mm.

[0049] Step three, the positive electrode round piece prepared in step one was used as the positive electrode, the zinc foil round piece prepared in step two was used as the negative electrode, the glass fiber membrane was used as the separator, the electrolyte was selected as 2M ZnS04+0.2M MnS04aqueous solution, the use amount was 120 μL, and the CR2032 type button cell aqueous zinc ion battery was assembled in the order of negative electrode shell, spring, gasket, zinc foil, separator, electrolyte, positive electrode, and positive electrode shell in the air environment using the battery packaging machine.

[0050] Example 5 Preparation of an aqueous zinc ion battery

[0051] Step one, preparation of the positive electrode: carbon nanotubes and F-ZnMn204 / CNT electrode material prepared in Example 2 were uniformly dispersed in 0.1wt% nanocellulose water dispersion after ultrasonic treatment, wherein the mass ratio of carbon nanotubes to nanocellulose was 2:1, and the dosage of the prepared F-ZnMn204 / CNT electrode material was 12.56 mg according to the size of the final electrode film. The solution was filtered into a film under the condition of negative pressure of 0.1 Mpa, and the positive electrode film was obtained after vacuum hot pressing drying at 80°C. The loading amount of F-ZnMn204 / CNT was 1 mg / cm 2 The final cutting was a positive electrode round piece with a diameter of 14 mm.

[0052] Step two, the zinc foil with a thickness of 150 μm and a purity of 99%~99.9% was polished with sandpaper to remove the surface oxide layer, and the polished zinc foil was cut into a round piece with a diameter of 12 mm.

[0053] Step three, using the positive electrode film prepared in step one as the positive electrode, the zinc foil prepared in step two as the negative electrode material, the glass fiber membrane as the separator, and the electrolyte selected as 2M ZnS04+0.2M MnS04, a CR2032 type button cell aqueous zinc ion battery was assembled in the order of negative electrode shell, spring, gasket, zinc foil, separator, electrolyte, positive electrode, and positive electrode shell in an air environment using a battery packaging machine.

[0054] Example 6 Preparation of an aqueous zinc ion battery

[0055] Step one, preparation of the positive electrode: carbon nanotubes and the F-ZnMn204 / CNT electrode material prepared in Example 3 were uniformly dispersed in a 0.1wt% nanocellulose water dispersion after ultrasonic treatment, the mass ratio of carbon nanotubes to nanocellulose was 2:1, the amount of the prepared F-ZnMn204 / CNT electrode material was 12.56mg according to the size of the final electrode film, and the solution was filtered into a film under the condition of a negative pressure of 0.1Mpa, and a positive electrode film was obtained after vacuum hot pressing and drying at 80°C, wherein the loading amount of F-ZnMn204 / CNT was 1mg / cm 2 The final cutting was a positive electrode film with a diameter of 14mm.

[0056] Step two, the zinc foil with a thickness of 150 μm and a purity of 99%~99.9% was polished with sandpaper to remove the surface oxide layer, and the polished zinc foil was cut into a disc with a diameter of 12mm.

[0057] Step three, using the positive electrode film prepared in step one as the positive electrode, the zinc foil prepared in step two as the negative electrode material, the glass fiber membrane as the separator, and the electrolyte selected as 2M ZnS04+0.2M MnS04, a CR2032 type button cell aqueous zinc ion battery was assembled in the order of negative electrode shell, spring, gasket, zinc foil, separator, electrolyte, positive electrode, and positive electrode shell in an air environment using a battery packaging machine.

[0058] Comparative Example 2 Preparation of an aqueous zinc ion battery

[0059] Step one, preparation of the positive electrode: carbon nanotubes and the F-ZnMn204 / CNT electrode material prepared in Example 3 were uniformly dispersed in a 0.1wt% nanocellulose water dispersion after ultrasonic treatment, the mass ratio of carbon nanotubes to nanocellulose was 2:1, the amount of the prepared F-ZnMn204 / CNT electrode material was 12.56mg according to the size of the final electrode film, and the solution was filtered into a film under the condition of a negative pressure of 0.1Mpa, and a positive electrode film was obtained after vacuum hot pressing and drying at 80°C, wherein the loading amount of F-ZnMn204 / CNT was 1mg / cm 2 The final cutting was a positive electrode film with a diameter of 14mm.

[0060] Step two, the zinc foil with a thickness of 150 μm and a purity of 99%~99.9% was polished with sandpaper to remove the surface oxide layer, and the polished zinc foil was cut into a disc with a diameter of 12mm.

[0061] Step 3: Using the positive electrode membrane prepared in Step 1 as the positive electrode, the zinc foil prepared in Step 2 as the negative electrode material, the glass fiber membrane as the separator, and the electrolyte being a 2M ZnSO4 + 0.2M MnSO4 aqueous solution, the CR2032 type button cell aqueous zinc-ion battery is assembled in air using a battery packaging machine in the following order: negative electrode shell, spring sheet, gasket, zinc foil, separator, electrolyte, positive electrode, and positive electrode shell.

[0062] Electrochemical performance (rate performance) tests were conducted on four types of aqueous zinc-ion batteries assembled according to Examples 4-6 and Comparative Example 2. The results are as follows: Figure 5 As shown, it can be concluded that Example 4 exhibits the best electrochemical performance, such as Figure 6 As shown, the aqueous zinc-ion battery of Example 4, at a current density of 3A / g, maintained a capacity retention of 96% after 1000 cycles, and had a discharge specific capacity as high as 335.2 mAh / g.

Claims

1. An electrode material, characterized by, The three-dimensional network matrix is composed of a plurality of carbon nanotubes crosslinked, and a plurality of polycrystalline microspheres distributed on the three-dimensional network matrix, wherein the polycrystalline microspheres are obtained by crystallization of a plurality of zinc manganate unit cells in which at least one oxygen element is replaced by a fluorine ion.

2. The electrode material of claim 1, wherein, The plurality of polycrystalline microspheres are combined with the carbon nanotubes of the three-dimensional network matrix by chemical bonds, and the oxygen element in 1 mol of zinc manganate unit cells is replaced by 3 mol of fluorine ions.

3. A method for producing the electrode material as claimed in claim 1 or 2, characterized in that The method comprises the following steps: 1) taking manganese acetate and zinc acetate, and dissolving them in ethanol; 2) adding carbon nanotubes and uniformly dispersing them; 3) adding a fluorine salt and uniformly stirring; 4) obtaining the target electrode material F-ZnMn2O4 / CNT through a hydrothermal reaction.

4. The production method according to claim 3, characterized by, In step 1, the molar ratio of zinc acetate to manganese acetate is 1:2, in step 2, the concentration of carbon nanotubes is 0.4 mg / mL, in step 3, the fluorine salt added is ammonium fluoride, the molar ratio of ammonium fluoride to zinc acetate is 1-4:1, and the stirring time is 30 min-60 min, in step 4, the temperature of the hydrothermal reaction is 180°C, and the reaction time is 12 h, after the hydrothermal reaction, the solution is cooled to room temperature, centrifuged and washed, and then dried to obtain the target electrode material, the centrifugation is performed at 13000 rpm for 15 min, the washing is performed by using deionized water and ethanol alternately, the centrifugation is performed for 3 times, and the solution is treated by vortexing and ultrasonic before centrifugation, and the drying is performed at 60-80°C for 4 h-6 h.

5. A positive electrode film characterized by comprising: The electrode material, carbon nanotubes and nanocellulose film are loaded in the nanocellulose film and uniformly distributed.

6. The positive electrode film according to claim 5, characterized by The mass ratio of carbon nanotubes to nanocellulose is 2:1, the loading amount of the electrode material on the nanocellulose film is 1 mg / cm², and the thickness of the nanocellulose film is 10-150 μm.

7. The method of producing the positive electrode film according to claim 5 or 6, characterized by, The method comprises the following steps: 1) taking the electrode material and carbon nanotubes prepared in claim 1 or 2, and ultrasonically dispersing them in a nanocellulose aqueous dispersion; 2) performing suction filtration to form a film, and drying to obtain a positive electrode film.

8. The preparation method according to claim 7, characterized in that, In step 1, the concentration of the nanocellulose aqueous dispersion is 0.1 wt%, and the concentration of the carbon nanotubes is 0.2 wt%, and in step 2, the drying is performed by hot-press vacuum drying at a temperature of 60-80°C for 10-12 h.

9. Use of the positive electrode film of claim 5 or 6 in the preparation of a battery.

10. Use according to claim 9, characterized in that, The battery is a water-based zinc ion battery, the positive electrode of the water-based zinc ion battery is the positive electrode film of claim 5 or 6, the negative electrode is a zinc sheet, the separator is a glass limiting separator, and the electrolyte is an aqueous solution of a zinc sulfate and manganese sulfate mixture with concentrations of 2M and 0.2M, respectively.

Citation Information

Patent Citations

  • Preparation method of green and environmental-friendly high-power aqueous zinc ion battery

    CN108306059A

  • Flexible electrode and preparation method and application thereof

    CN117153998A

  • Preparation and application of sodium vanadyl fluorophosphate composite microspheres constructed by one-dimensional carbon nanotubes and supported by three-dimensional network skeleton

    CN118771345A

  • KR20250059586A